The achievement of American liberalism : the New Deal and its legacies - Chafe, William H., 1942- (Columbia University Press, 2003)
Alan Brinkley, Melvin Urofsky, Harvard Sitkoff, and other leading scholars explore the liberal tradition in American politics, culture, and social relations.